PERAN PEREMPUAN DALAM PENGENTASAN KEMISKINAN DI DESA LETMAN, KABUPATEN MALUKU TENGGARA - Nilda Wati Tukloy; Wardis Girsang; Felecia. P. Adam (Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Mataram, 2025)
ABSTRACT This study aims to examine the role of women in poverty alleviation in Letman Village, Southeast Maluku Regency. The data collection technique used in this study was simple random sampling, resulting in a sample of 30 respondents. Data were collected through the distribution of questionnaires and direct interviews with participants. The data analysis method employed was descriptive qualitative analysis using both primary and secondary data. This research was conducted in Letman Village, Southeast Maluku Regency, over the course of one month, from December 2024 to January 2025. The results of the analysis show that women’s roles in poverty alleviation in Letman Village are more prominent in both domestic and public activities (13.83%). Furthermore, women contribute significantly to household income and expenditure, accounting for 40.05% of income and 37.23% of expenditure. Household budget allocation shows a greater portion directed toward non-food needs (33.85%) compared to food. This indicates that women play a more dominant role in poverty alleviation in this village compared to men, as women are also capable of supporting men in fulfilling daily and household needs.